2006
DOI: 10.1016/j.febslet.2006.04.091
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid control of nitric oxide production by macrophages

Abstract: Modulation of macrophage functions by fatty acids (FA) has been studied by several groups, but the effect of FA on nitric oxide production by macrophages has been poorly examined. In the present study the effect of palmitic, stearic, oleic, linoleic, arachidonic, docosahexaenoic and eicosapentaenoic acids on NF-jB activity and NO production in J774 cells (a murine macrophage cell line) was investigated. All FA tested stimulated NO production at low doses (1-10 lM) and inhibited it at high doses (50-200 lM). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 62 publications
(66 reference statements)
5
32
0
Order By: Relevance
“…Most of them have shown that FAs inhibit NF-κB DNA-binding activity in macrophages [53,[63][64][65], and similar results have been observed by our group [66]. There is evidence, however, that saturated FAs induce NF-κB activation, and this effect may be related to the inflammatory changes observed in adipocyte and macrophage interactions [67].…”
Section: Nf-κbsupporting
confidence: 85%
“…Most of them have shown that FAs inhibit NF-κB DNA-binding activity in macrophages [53,[63][64][65], and similar results have been observed by our group [66]. There is evidence, however, that saturated FAs induce NF-κB activation, and this effect may be related to the inflammatory changes observed in adipocyte and macrophage interactions [67].…”
Section: Nf-κbsupporting
confidence: 85%
“…Our and other studies observed a decrease in the LPS-induced production of proinflammatory cytokines and NO by monocytes and macrophages after exposure to LA [16,25]. It is noteworthy that our data showed that GLA has more potent effective than LA in modulating the production of proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 44%
“…Research from the last 30 years has shown that fatty acids (FAs), despite their simple structure, can modulate many macrophage functions, including adhesion and phagocyte capacity [1,2], production of reactive oxygen and nitrogen species [3][4][5] and cytokine release [6][7][8][9]. Among the cytokine modulated by FA, tumor necrosis factor (TNF-a) is of great interest due to its role in the inflammation process observed in several diseases such as rheumatoid arthritis, atherosclerosis, and obesity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%